Reconstruction of Temporomandibular Joint and Skull Base Defect Following Osteosarcoma Resection - Machoň, Vladimír; Vlachopulos, Vasilis; Beňo, Michal (The Journal of craniofacial surgery, 2022)
Osteosarcoma of the jaw is uncommon, occurring in about 6% to 8% of cases. The authors present the case report of a (woman 72-year-old) with osteosarcoma involving the temporomandibular joint (TMJ). Radical surgery was chosen with resection of the tumor together with the condyle, the coronoid process, the zygomatic arch and eroded bone of the skull base at the site of the joint cavity. Contact of the tumor with the dura mater was not confirmed perioperatively.Reconstruction of the TMJ was 24 months after resection. The fossa component was concurrently formed in such a way as to cover the defect in the skull base and allow the reconstruction of the fossa and resected zygomatic arch. Four years after tumor resection there are no signs of local recurrence or metastases. Two years after TMJ reconstruction, the patient is symptom-free-occlusion is satisfactory, jaw movement is within normal range.
Keywords: Skull Base; Female; nemoci temporomandibulárního kloubu; baze lební; lidé; Osteosarcoma; Aged; Temporomandibular Joint; ženské pohlaví; temporomandibulární kloub; osteosarkom; Joint Prosthesis; Temporomandibular Joint Disorders; Humans; senioři; protézy kloubů